Norms for fitness, performance, and health - Hoffman, Jay 1961- (Human Kinetics, 2006)
"Norms for Fitness, Performance, and Health contains a comprehensive collection of normative data for numerous fitness, performance, and health components across a range of ages, abilities, occupations, and athletic backgrounds. It lays the foundation for working with normative data by detailing the purpose and benefits of norms. It reviews relevant statistical information to assist the reader in understanding and interpreting descriptive statistics, including a limited discussion on inferential statistics."--Jacket